Ecology of ants along elevational rainforest gradients in the tropics - Moses, Jimmy (Jihočeská univerzita, 2021)
The thesis investigates the community ecology and species diversity of tropical ants on tropical mountains. The primary focus is on the changes in the ground-dwelling ant communities along elevational rainforest gradients, and how their elevational patterns are influenced by various biotic and abiotic factors. First, we investigated how elevation, leaf litter depth and their interaction affect the abundance, species richness and composition of ground-dwelling ants on Mt. Wilhelm (Papua New Guinea). Next, we investigated how ant communities change with forest succession in time along an extensive tropical elevational gradient in Southern Papua New Guinea. The aim was to assess both spatial and temporal trends in the ant communities and whether these changes could serve as indicators towards ecological recovery after human-induced forest disturbance. Finally, we assessed the relationships of ant species richness and activity, and their relative use of six nutrients, with elevation and season in three different tropical mountain regions (New Guinea,Tanzania and Ecuador).
Ecology of ants along elevational rainforest gradients in the tropics
Keywords: ants; elevational gradients; altitude; tropical forests; nutrient use; leaf-litter; succession; abiotic factors; biotic factors; community ecology; species richness.; ants; elevational gradients; altitude; tropical forests; nutrient use; leaf-litter; succession; abiotic factors; biotic factors; community ecology; species richness.